PENGARUH MODEL PEMBELAJARAN TALKING STICK DENGAN METODE MATH MAGIC TERHADAP HASIL BELAJAR MATEMATIKA PADA POKOK BAHASAN KUBUS DAN BALOK DI KELAS V SD NEGERI 200211 PADANG SIDIMPUAN - Rizqi Jamiah; Edy Surya (State Islamic University of North Sumatra, 2016)
This study aims to determine the effect of significant between learningmodels talking stick method to the magic math mathematics learningoutcomes in the classroom digunaakan V. This type of research isquantitative research with experimental methods of classic experimentaldesign types (classical experimental design), which was held inElementary School 200 211 Padangsidimpuan. The population in thisstudy consisted of all students in fifth grade elementary totaling 82people, and also the whole population sample. The research instrumentsused were pretest and posttest. Statistical hypothesis testing formulaused t-test, and the results of hypothesis test obtained by the average -average grade control = 67, average - average class experiment = 76,and t test with a value of t = 2.32> t table = 1.990. So we concluded thatHo is rejected and Ha accepted, which means there is significantinfluence between the learning model talking stick method on learningoutcomes magic math mathematics on the subject of cubes and blocksclass V SD Negeri 200 211 Padangsidimpuan.